How do you solve \[\dfrac{x-3}{x-4}=\dfrac{x-5}{x+4}\]?
Answer
Verified
442.2k+ views
Hint: From the question given, we have been asked to solve \[\dfrac{x-3}{x-4}=\dfrac{x-5}{x+4}\].We can solve the given equation by transforming it and then simplifying the equation. By doing this, we can get the solution for the given question. We can clearly say that the values of \[\left( x-4 \right)\text{ and }\left( x+4 \right)\] will not be equal to zero, because if the values of \[\left( x-4 \right)\text{ and }\left( x+4 \right)\] will be zero, then the given equation will become undefined.
Complete step by step solution:
From the question, we have been given that \[\dfrac{x-3}{x-4}=\dfrac{x-5}{x+4}\]
Now, multiply both sides of the equation with \[\left( x-4 \right)\left( x+4 \right)\].
By multiplying the both sides of the equation with \[\left( x-4 \right)\left( x+4 \right)\], we get
\[\Rightarrow \dfrac{x-3}{x-4}\left( x-4 \right)\left( x+4 \right)=\dfrac{x-5}{x+4}\left( x-4 \right)\left( x+4 \right)\]
On further more simplifying the above equation we get \[\Rightarrow \left( x-3 \right)\left( x+4 \right)=\left( x-5 \right)\left( x-4 \right)\]
Now, simplify the equation by multiplying all the terms.
By multiplying the terms, we get \[\Rightarrow {{x}^{2}}+x-12={{x}^{2}}-9x+20\]
Now, simplify the equation further more.
Shift \[{{x}^{2}}\] in the right hand side of the equation to the left hand side of the equation.
B y shifting \[{{x}^{2}}\] from the right hand side of the equation to the left hand side of the equation, we get \[\Rightarrow {{x}^{2}}-{{x}^{2}}+x-12=-9x+20\]
By the cancellation of terms, we get \[\Rightarrow x-12=-9x+20\]
Shift whole right hand side terms to the left hand side of the equation.
By shifting, we get
\[\Rightarrow x-12+9x-20=0\]
\[\Rightarrow 10x-32=0\]
Now, shift \[-32\] to the right hand side of the equation. By shifting we get,
\[\Rightarrow 10x=32\]
\[\Rightarrow x=\dfrac{32}{10}\]
\[\Rightarrow x=\dfrac{16}{5}\]
Hence, the given equation is solved.
Note: We should be very careful while doing the calculation in this problem. Also, we should be very careful while solving the equation. Also, we should be very careful while transforming the equation. Also, we should do exact transformations to the given equation to obtain the perfect answer. Similarly we can solve \[\begin{align}
& \dfrac{x-9}{x-5}=\dfrac{x-3}{x+5}\Rightarrow \left( x-9 \right)\left( x+5 \right)=\left( x-3 \right)\left( x-5 \right)\Rightarrow {{x}^{2}}-4x-45={{x}^{2}}-8x+15\Rightarrow -45=-4x+15 \\
& \Rightarrow 4x=60\Rightarrow x=15 \\
\end{align}\]
Complete step by step solution:
From the question, we have been given that \[\dfrac{x-3}{x-4}=\dfrac{x-5}{x+4}\]
Now, multiply both sides of the equation with \[\left( x-4 \right)\left( x+4 \right)\].
By multiplying the both sides of the equation with \[\left( x-4 \right)\left( x+4 \right)\], we get
\[\Rightarrow \dfrac{x-3}{x-4}\left( x-4 \right)\left( x+4 \right)=\dfrac{x-5}{x+4}\left( x-4 \right)\left( x+4 \right)\]
On further more simplifying the above equation we get \[\Rightarrow \left( x-3 \right)\left( x+4 \right)=\left( x-5 \right)\left( x-4 \right)\]
Now, simplify the equation by multiplying all the terms.
By multiplying the terms, we get \[\Rightarrow {{x}^{2}}+x-12={{x}^{2}}-9x+20\]
Now, simplify the equation further more.
Shift \[{{x}^{2}}\] in the right hand side of the equation to the left hand side of the equation.
B y shifting \[{{x}^{2}}\] from the right hand side of the equation to the left hand side of the equation, we get \[\Rightarrow {{x}^{2}}-{{x}^{2}}+x-12=-9x+20\]
By the cancellation of terms, we get \[\Rightarrow x-12=-9x+20\]
Shift whole right hand side terms to the left hand side of the equation.
By shifting, we get
\[\Rightarrow x-12+9x-20=0\]
\[\Rightarrow 10x-32=0\]
Now, shift \[-32\] to the right hand side of the equation. By shifting we get,
\[\Rightarrow 10x=32\]
\[\Rightarrow x=\dfrac{32}{10}\]
\[\Rightarrow x=\dfrac{16}{5}\]
Hence, the given equation is solved.
Note: We should be very careful while doing the calculation in this problem. Also, we should be very careful while solving the equation. Also, we should be very careful while transforming the equation. Also, we should do exact transformations to the given equation to obtain the perfect answer. Similarly we can solve \[\begin{align}
& \dfrac{x-9}{x-5}=\dfrac{x-3}{x+5}\Rightarrow \left( x-9 \right)\left( x+5 \right)=\left( x-3 \right)\left( x-5 \right)\Rightarrow {{x}^{2}}-4x-45={{x}^{2}}-8x+15\Rightarrow -45=-4x+15 \\
& \Rightarrow 4x=60\Rightarrow x=15 \\
\end{align}\]
Recently Updated Pages
What percentage of the area in India is covered by class 10 social science CBSE
The area of a 6m wide road outside a garden in all class 10 maths CBSE
What is the electric flux through a cube of side 1 class 10 physics CBSE
If one root of x2 x k 0 maybe the square of the other class 10 maths CBSE
The radius and height of a cylinder are in the ratio class 10 maths CBSE
An almirah is sold for 5400 Rs after allowing a discount class 10 maths CBSE
Trending doubts
The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths
Why is there a time difference of about 5 hours between class 10 social science CBSE
Change the following sentences into negative and interrogative class 10 english CBSE
Write a letter to the principal requesting him to grant class 10 english CBSE
Explain the Treaty of Vienna of 1815 class 10 social science CBSE
Write an application to the principal requesting five class 10 english CBSE